2003
DOI: 10.1016/s0168-6496(03)00032-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of group-specific oligonucleotide probes for quantitative analysis of intestinal ecosystems: their application to assessment of equine colonic microflora

Abstract: Nine oligonucleotide probes complementary to conserved regions of small subunit rRNA from phylogenetically defined clusters of intestinal anaerobic bacteria were designed and evaluated for use in quantitative analysis of intestinal microflora. Optimum wash temperatures (T w ) were determined according to the temperature of dissociation (T d ) of each probe and target group specificity was demonstrated by comparing hybridisation to target and non-target rRNA immobilised on nylon membranes. Three probes are targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 65 publications
(194 reference statements)
3
40
0
3
Order By: Relevance
“…The relative abundance of Clostridium cluster XIV, as determined using probe Erec 482, varied from 8 to 27% for the rumen samples (Table 2). These data are in agreement with the study of Daly and Shirazi-Beechey (8), in which the abundance of cluster XIV as determined with the same probe (Erec 482) was found to represent the highest proportion of rRNA found in any one of the equine intestinal samples studied (28%). The abundance of cluster XIV clostridia was found to vary greatly in their study, and this was also the case here.…”
Section: Vol 76 2010 Microbial Community Composition In Landfill 1303supporting
confidence: 92%
See 2 more Smart Citations
“…The relative abundance of Clostridium cluster XIV, as determined using probe Erec 482, varied from 8 to 27% for the rumen samples (Table 2). These data are in agreement with the study of Daly and Shirazi-Beechey (8), in which the abundance of cluster XIV as determined with the same probe (Erec 482) was found to represent the highest proportion of rRNA found in any one of the equine intestinal samples studied (28%). The abundance of cluster XIV clostridia was found to vary greatly in their study, and this was also the case here.…”
Section: Vol 76 2010 Microbial Community Composition In Landfill 1303supporting
confidence: 92%
“…2), a very low hybridization signal was obtained for rumen fluid samples. Clostridium cluster III has been quantified in equine colonic samples, and the relative abundance varied from 1.3% to 3.0% of the total rRNA (8). It may be, therefore, that the relative proportion of cluster III clostridia is also low in the rumen fluid samples analyzed here and abundances of 1 to 3% are below the threshold for accurate quantification.…”
Section: Vol 76 2010 Microbial Community Composition In Landfill 1303mentioning
confidence: 75%
See 1 more Smart Citation
“…This method has been used to quantify rRNA from samples of human, horse and rumen (Sghir et al, 2000;Marteau et al, 2001;Daly and Shirazi -Beechey, 2003). Because PCR has no relation to other amplification methods, quantification determination is more accurate, and therefore, this method has a good reputation and is widely used.…”
Section: The Dot Blot Electrophoresis Methodsmentioning
confidence: 99%
“…Using molecular analysis, Daly et al (2001) reported that 89% of the recovered sequences did not correspond to any recorded ones, suggesting that the anaerobic microflora of the equine large intestine are underrepresented and that the equine flora may contain many novel bacterial species. In a latter study, Daly and Shirazi-Beechey (2003), using specific oligonucleotide probes, quantitatively analyzed the intestinal microflora and obtained the first data of predominant bacterial populations in the large intestine of horses. The results showed that the strains Spirochaetaceae, Cytophaga-Flexibacter-Bacteroides, the group EubacteriumClostridium rectal Coccoidea and an 'unknown cluster C' of clostridiaceae were the largest populations in the cecumcolon, each group comprising 10% to 30% of the total microflora in examined horses.…”
Section: Passage Ratementioning
confidence: 99%